Analysis of the dynamics between supply chain flexibility and key management ratios. (27th January 2009) - More, Dileep; Subash Babu, A.
Managing flexibility in supply chains involves a variety of actions, at various stages of designing, using and improving the supply chain system. This problem has very close association with various financial factors in business and therefore with the Key Management Ratios (KMRs) which are of considerable interest to corporate managers. The language of money binds various segments of any supply chain, in which the operational managers are busy dealing with information flow and material flow, to facilitate the desired cash flow to happen. Business management ratios are considered as the guiding stars for corporate managers as they are believed to capture the real status of the business, under different scenarios. However, as far as the Supply Chain Flexibility (SCF) is concerned, these two issues are not discussed jointly. There are many types of supply chain flexibilities and various KMRs. It is perhaps difficult to establish generalised relationships between these two sets of entities. A study was carried out to assess the influence that may be exerted by various types of SCF on the elements of KMRs and eventually, the KMRs themselves, the findings of which are reported in this paper.